2018
DOI: 10.3390/toxins10100413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Bioactivity of a Novel Broad-Spectrum Antimicrobial Peptide Brevinin-1GHa from the Frog Skin Secretion of Hylarana guentheri and Its Analogues

Abstract: Many antimicrobial peptides (AMPs) have been identified from the skin secretion of the frog Hylarana guentheri (H.guentheri), including Temporin, Brevinin-1, and Brevinin-2. In this study, an antimicrobial peptide named Brevinin-1GHa was identified for the first time by using ‘shotgun’ cloning. The primary structure was also confirmed through mass spectral analysis of the skin secretion purified by reversed-phase high-performance liquid chromatography (RP-HPLC). There was a Rana-box (CKISKKC) in the C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…As the NCBI-BLAST alignment suggested, this novel peptide shared similar properties with most peptides in the Brevinin-1 subfamily. Among these, Brevinin-1GHd is 83% identical with Brevinin-1GHa and 71% identical with Gaegurin-5 [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the NCBI-BLAST alignment suggested, this novel peptide shared similar properties with most peptides in the Brevinin-1 subfamily. Among these, Brevinin-1GHd is 83% identical with Brevinin-1GHa and 71% identical with Gaegurin-5 [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, one novel Brevinin-1 type peptide, Brevinin-1GHa, was first found in Hylarana guentheri and two analogs, Brevinin-1GHb and Brevinin-1GHc, were designed to further study the relationships between structure and activity. The study of Brevinin-1GHa and its two analogs revealed that the deletion or removal of the "Rana-Box" decreased its antimicrobial activity while reducing hemolytic activity [13]. Through comparing differences of structure and activity between Brevinin-1GHa and its analogs, the hypothesis was established that the hemolytic activity was determined both by the hydrophobicity and hydrophobic face since the lack and decrease in hydrophobicity of Brevinin-1GHb and Brevinin-1GHc showed lower hemolytic activity than Brevinin-1GHa [13].…”
Section: Hemolysis and Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…This characteristic makes them to have extreme chemical diversity [7,8]. Till now, several biochemical arsenals with potential pharmaceutical properties, particularly antimicrobial peptides (AMPs), have been discovered from the skin secretions of amphibians [9][10][11][12][13][14]. Despite this, little information is available about amphibian skin-derived bioactive compounds with wound healing activity.…”
Section: Discussionmentioning
confidence: 99%